Visual aids in ambulatory clinical practice: Experiences, perceptions and needs of patients and healthcare professionals - Hafner, Catherine; Schneider, Julie; Schindler, Mélinée; Braillard, Olivia (PLOS ONE, 2022)
This study aims to explore how visual aids (VA) are used in ambulatory medical practice. Our research group (two doctors, one graphic designer and one sociologist) have led a qualitative study based on Focus Groups. A semi-structured guide and examples of VA were used to stimulate discussions. Participants were healthcare professionals (HP) working in ambulatory practice in Geneva and French-speaking outpatients. After inductive thematic analysis, the coding process was analyzed and modified to eventually reach consensus. Six focus groups gathered twenty-one HP and fifteen patients. Our study underlines the variety of purposes of use of VA and the different contexts of use allowing the distinction between “stand-alone” VA used out of consultation by patients alone and “interactive” VA used during a consultation enriched by the interaction between HP and patients. HP described that VA can take the form of useful tools for education and communication during consultation. They have questioned the quality of available VA and complained about restricted access to them. Patients expressed concern about the impact of VA on the interaction with HP. Participants agreed on the beneficial role of VA to supplement verbal explanation and text. Our study emphasizes the need to classify available VA, guarantee their quality, facilitate their access and deliver pertinent instructions for use.